2003
DOI: 10.1086/367846
|View full text |Cite
|
Sign up to set email alerts
|

Fine Mapping of Autistic Disorder to Chromosome 15q11-q13 by Use of Phenotypic Subtypes

Abstract: Autistic disorder (AutD) is a complex genetic disease. Available evidence suggests that several genes contribute to the underlying genetic risk for the development of AutD. However, both etiologic heterogeneity and genetic heterogeneity confound the discovery of AutD-susceptibility genes. Chromosome 15q11-q13 has been identified as a strong candidate region on the basis of both the frequent occurrence of chromosomal abnormalities in that region and numerous suggestive linkage and association findings. Ordered-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

19
255
0
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 307 publications
(276 citation statements)
references
References 67 publications
19
255
0
2
Order By: Relevance
“…The 7q linkage result, coupled with literature support for an autism susceptibility gene within 15 cM of the original QTL region, 5,7,10,11,34 prompted us to investigate the possibility of increased heterogeneity in the enlarged sample. Based on the novel work by Shao et al, 20 who described the use of phenotypic subtypes to identify homogeneous subsets of autism families, we applied the OSA approach to the language traits and obtained encouraging results. First, the linkage statistic for the qualitative analysis increased substantially by ranking the families according to the language covariates.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…The 7q linkage result, coupled with literature support for an autism susceptibility gene within 15 cM of the original QTL region, 5,7,10,11,34 prompted us to investigate the possibility of increased heterogeneity in the enlarged sample. Based on the novel work by Shao et al, 20 who described the use of phenotypic subtypes to identify homogeneous subsets of autism families, we applied the OSA approach to the language traits and obtained encouraging results. First, the linkage statistic for the qualitative analysis increased substantially by ranking the families according to the language covariates.…”
Section: Discussionmentioning
confidence: 97%
“…Investigators have begun to use these autism endophenotypes as covariates in linkage analyses in an attempt to increase both phenotypic and genetic homogeneity of the affected sample. [18][19][20][21] For example, Buxbaum et al 19 reported that most of the linkage evidence for a putative autism susceptibility locus on chromosome 2q was from the families with a language delay. These results were supported in an independent sample of 82 families with autism.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…40,[119][120][121][122][123][124][125][126][127][128][129][130][131][132][133][134][135][136][137] Research groups, study design and main findings of linkage studies that reported positive results are summarized in Table 1 for genome-wide linkage and association studies with a qualitative AD phenotype, and in Table 2 for linkage studies with either a quantitative phenotype, a specific qualitative endophenotype, or other specific linkage models. 122,123,127,130,[138][139][140][141][142][143][144][145][146][147][148] From Table 1, it can be seen that linkage has been found in at least two independent studies in regions 2q, 3q25-27, 3p25, 6q14-21, 7q31-36 and 17q11-21.…”
Section: Linkage Studiesmentioning
confidence: 98%
“…144 Orderedsubset analysis regarding the phenotype insistence on sameness has resulted in significant linkage at chromosome 15q11-13. 147 Owing to the disappointing findings regarding the X-chromosome, other approaches have been chosen to elucidate the skewed sex distribution of AD. In two independent samples, two loci on 17q did show significant linkage in male only pairs.…”
Section: Linkage Studiesmentioning
confidence: 99%